Striking the Match: A (Non-)Materialist Rhetoric of the 2012 Chicago Teachers Strike - Conklin, Elyse (Wake Forest University, 2017)
STRIKING THE MATCH: A (NON-)MATERIALIST RHETORIC OF THE 2012 CHICAGO TEACHERS STRIKE
Keywords: Communication Studies; Critical Economic/Affect Theory; Education Policy